2018
DOI: 10.2478/ama-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D Simulation to Design Theoretical and Real Pipe Inspection Mobile Robot Model

Abstract: The main aim of the paper is to present the process of design pipe inspection mobile robot by using 3D simulations. Next methods and processes of making designed components was described. Finally, functional tests of a constructed real robot model such as speed tests, inclined pipe test was carried out. The robot was specifically designed to inspect sewer pipelines. The mobile robot is equipped with a vision system. The structure of the pipe inspection robot allows adjustments to the geometrical parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Furthermore, in the case of AGV robots, the precision of the final positioning is crucial for successful loading and unloading of transported goods in typical industrial applications [ 20 ]. Designers of robotics systems use advanced tools to assist in the design process of control systems [ 21 , 22 , 23 , 24 , 25 ] to provide the expected functionality of the robot. The working environment has a particular impact on the change in the operating parameters of the robot.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, in the case of AGV robots, the precision of the final positioning is crucial for successful loading and unloading of transported goods in typical industrial applications [ 20 ]. Designers of robotics systems use advanced tools to assist in the design process of control systems [ 21 , 22 , 23 , 24 , 25 ] to provide the expected functionality of the robot. The working environment has a particular impact on the change in the operating parameters of the robot.…”
Section: Related Workmentioning
confidence: 99%
“…In their approach, the inspection data collected by the mobile robot-based platform could support and be used to design the repairing strategy and the respective robot path. More research focusing on the techniques and applications related to the mobile robot-based platform for structural damage inspection and various purposes has been widely conducted as presented in Table 3, such as non-structural damage inspection, 94 pipeline inspection, 95,96 localization techniques of inspection-aimed mobile robots. 97 These previous studies demonstrated that increasing attention is paid to mobile robot technology which can be applied in practice for damage inspection in various scenarios, and is able to perform more tasks, such as repair of pipelines.…”
Section: Mobile Robot Application In Damage Inspectionmentioning
confidence: 99%
“…In their approach, the inspection data collected by the mobile robot‐based platform could support and be used to design the repairing strategy and the respective robot path. More research focusing on the techniques and applications related to the mobile robot‐based platform for structural damage inspection and various purposes has been widely conducted as presented in Table 3, such as non‐structural damage inspection, 94 pipeline inspection, 95,96 localization techniques of inspection‐aimed mobile robots 97 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the structural analysis carried out at the stage of construction of the support frame of the mobile module in the initial variant of the developed model, and on the basis of experience gained during the assembly of the frame, it was found necessary to introduce changes in the detailed design and assembly of this module [2,4]. The basic and most important change was the modernization of the support frame.…”
Section: Drive Modulementioning
confidence: 99%